2018
DOI: 10.1016/j.jechem.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Highly reversible lead-carbon battery anode with lead grafting on the carbon surface

Abstract: A novel C/Pb composite has been successfully prepared by electroless plating to reduce the hydrogen evolution and achieve the high reversibility of the anode of lead-carbon battery (LCB). The deposited lead on the surface of C/Pb composite was found to be uniform and adherent to carbon surface. Because lead has been stuck on the surface of C/Pb composite, the embedded structure suppresses the hydrogen evolution of lead-carbon anode and strengthens the connection between carbon additive and sponge lead. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…[ 1 ] Among various rechargeable batteries and supercapacitors, aqueous electrochemical energy storage systems are preferred due to their high safety and low capital cost. [ 2 ] However, commercial aqueous lead‐ and nickel‐based rechargeable batteries possess low energy densities (≈45 Wh kg −1 for Pb–acid batteries; [ 3 ] ≈50 Wh kg −1 for Ni–Cd batteries [ 4 ] ) and limited life spans, which increases the energy storage cost per unit energy output, [ 5,6 ] thus limits their practical applications. Zinc metal is considered as an ideal anode for aqueous energy storage devices because of its high theoretical capacity (gravimetric, 820 mAh g −1 ; volumetric, 5851 mAh cm −3 ), low potential (−0.76 V vs standard hydrogen electrode (SHE)), and high hydrogen evolution overpotential.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1 ] Among various rechargeable batteries and supercapacitors, aqueous electrochemical energy storage systems are preferred due to their high safety and low capital cost. [ 2 ] However, commercial aqueous lead‐ and nickel‐based rechargeable batteries possess low energy densities (≈45 Wh kg −1 for Pb–acid batteries; [ 3 ] ≈50 Wh kg −1 for Ni–Cd batteries [ 4 ] ) and limited life spans, which increases the energy storage cost per unit energy output, [ 5,6 ] thus limits their practical applications. Zinc metal is considered as an ideal anode for aqueous energy storage devices because of its high theoretical capacity (gravimetric, 820 mAh g −1 ; volumetric, 5851 mAh cm −3 ), low potential (−0.76 V vs standard hydrogen electrode (SHE)), and high hydrogen evolution overpotential.…”
Section: Introductionmentioning
confidence: 99%
“…The change of the morphology and crystallinity of lead and lead sulfate on the negative electrode surface will lead to sulfation [14]. Due to the poor conductivity of PbSO 4 , the accumulation of lead sulfate will lead to the reduction of the electrode active area, increase the reaction resistance, thus increasing the difficulty of the transformation of the active substances.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there is no information on how the impedance results were obtained when the content was more than 1 wt%, as well as the discharge and total polarization results when the content was greater than 0.1 wt%. Nevertheless, attempts were made to improve the performance of battery electrodes using carbonaceous materials, [34][35][36][37][38][39][40][41][42][43] and the effect was confirmed in the FeS 2 cathode of thermal batteries. However, additional validation is required for actual mass production.…”
Section: Fesmentioning
confidence: 99%
“…13) Carboneous materials have been extensively studied and used as additives for electrodes in rechargeable Li-ion batteries. [34][35][36][37][38][39][40][41][42][43] Among them, some carboneous materials are used as current collectors and as electrode supports without adding other binder materials. 34,[49][50][51][52][53][54] Noda et al showed that electrodes containing 99 wt% of active materials and 1 wt% CNTs can be produced.…”
Section: Fesmentioning
confidence: 99%